1990
DOI: 10.1159/000125340
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Adrenocorticotropin Release during Wallerian Degeneration of Peripheral Sympathetic Neurons after Superior Cervical Ganglionectomy of Rats

Abstract: The changes in adrenocorticotropin (ACTH) release before, during and after sympathetic nerve degeneration following superior cervical ganglionectomy (SCGx) were examined in male rats. A 12-fold increase of circulating ACTH was found in both SCGx and sham-operated rats 6 h after surgery. In sham-operated rats, plasma ACTH decreased by about half 16–22 h after surgery, whereas in SCGx rats it remained at a high concentration from 16 to 54 h after surgery, attaining basal values by 120 h post-SCGx. In SCGx rats, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
11
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
4
11
0
Order By: Relevance
“…Differentially plasma ACTH levels increased during wallerian degeneration of the adrenergic terminals after superior cervical ganglionectomy, as shown by earlier work in the literature [30]. After chronic surgery no changes in plasma prolactin and GH levels were observed, as in previous studies [4,9].…”
Section: Discussionsupporting
confidence: 80%
“…Differentially plasma ACTH levels increased during wallerian degeneration of the adrenergic terminals after superior cervical ganglionectomy, as shown by earlier work in the literature [30]. After chronic surgery no changes in plasma prolactin and GH levels were observed, as in previous studies [4,9].…”
Section: Discussionsupporting
confidence: 80%
“…It must be noted that as far as surgical stress was concerned, precautions were routinely taken in the present experiments to introduce the same type of stress in both the experimental and sham-operated groups, except for ganglion removal. That the resulting surgical stress was presumably the same in SCGx and sham SCGx rats was indicated by a similar increase in plasma ACTH levels and a similar hypothalamic concentration of CRH and AVP reported in both groups of animals 6 h after surgery [21 ].…”
Section: Discussionsupporting
confidence: 61%
“…The results ob tained indicate that a prior Px did not modify the changes in AVP release found 6 or 16 h after SCG ablation. Thus, as in the case of gonadotropin [23], prolactin [23] and ACTH re lease [21], SCG neurons modify AVP release from NIL by a mechanism independent of the pineal gland, most presum ably linked to an intrapituitary effect.…”
Section: Discussionmentioning
confidence: 95%
“…In a study designed to examine the levels of serum growth hormone (GH) and PRL, and of MBH GH-releasing hormone (GHRH), thyrotropin-releasing hormone (TRH) and somato-statin, from 16 h to 7 days after bilateral SCGx of adult male rats (35) we reported significantly lower serum GH and PRL, and higher MBH GHRH and TRH levels as compared to controls during the Wallerian degeneration phase; MBH somatostatin concentration decreased in SCGx rats. The data, together with the previously observed decrease in MBH corticotropin-releasing hormone (CRH) and arginine vasopressin (AVP) content found in SCGx rats during the Wallerian degeneration phase (36), as well as with the LHRH data mentioned above, indicated that a modulator/ role of peripheral sympathetic nerve terminals is exerted on hypophysiotropic hormone release. A previous Px did not modify the changes in hypophysiotropic or hypophyseal hormone release found during the Wallerian degeneration phase after SCGx.…”
supporting
confidence: 57%